Perspectives on Passion in Sport Management Research - Marshall Magnusen (Journal of Applied Sports Management, 2024)
The focus of this special issue is to continue to broaden discussions of passion in sports to management contexts with sport personnel rather than marketing contexts with sport consumers. This is done through an offering of several “think pieces” with the goal of inspiring new and creative scholarship about passion in sport work environments.
Keywords: CSR; grit; employees; job seekers; organizational behavior